Syntax-Pragmatics Interface: Mandarin Chinese Wh-the-hell and Point-of-View Operator - Chou, Chao-Ting Tim (Syntax (Oxford, England), 2012)
.  Based on previously unnoted data concerning wh‐the‐hell attitude‐bearing questions in Mandarin Chinese, I argue that integrating the pragmatic notion “point of view” into the syntactic computation enables us to capture certain properties of wh‐the‐hell questions in Mandarin Chinese in a systematic and illuminating way. The two central phenomena analyzed are (1) causal zenme‘how come’ is not compatible with daodi‘the‐hell’ in Chinese, and (2) in Chinese wh‐the‐hell questions, when daodi‘the‐hell’ takes matrix scope while staying overtly in the embedded clause, the person feature of the matrix subject cannot be third person. I argue that explaining these phenomena depends on recognizing the logophoricity of the negative attitudes carried by daodi and causal zenme. The valuation relation that I postulate between the Point‐of‐View operator and an unvalued Point‐of‐View feature of daodi and causal zenme not only explains these data but also formally captures certain properties of the Chinese logophor ziji (cf. Huang & Liu 2001).